Classification of different types of metal from recyclable household waste for automatic waste separation system - Siti Hajar Yusoff; Sazali Mahat; Nur Shahida Midi; Sarah Yasmin Mohamad; Syasya Azra Zaini (Institute of Advanced Engineering and Science, 2019)
Nowadays, solid waste has become a major problem in Malaysia. However, most people in Malaysia are not aware and take this problem for granted. The rising number of population and massive development in recent years indirectly generated an enormous value of household waste, making the household waste the main generator for solid waste in Malaysia. It stated that only 5 percent of an average 30,000 tons of waste have been recycled in Malaysia. The purpose of the paper is to design a system to separate the metal recyclable household waste automatically and record the data waste collected. There are total of four detectors used to separate the non-metal, steel, copper and aluminum metal waste. The average time used to complete metal separation process by using the proposed prototype is 14.5 seconds. This paper includes a mechanical part, programming part, an electronic design and also the data collected from this proposed system. The system will be programmed using Arduino Mega as a microcontroller to control all the electronic component in the system.